MANAJEMEN KONFLIK KELUARGA NABI ADAM AS DAN KELUARGANYA - Bakhri, Amirul (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This paper seeks to reveal the problems of conflict that occurred in the Prophet Adam and the family in the Qur'an. In discussing this issue there are several points to be discussed: the conflict of creation of Prophet Adam which was responded to be troubled by angels, the conflict of Adam and his wife Eve who was seduced by the Devil, the story of the Prophet Adam and his wife Eve, the sacrificial conflict event perpetrated by his son Adam namely Qabil and Abel. Discussion with a narrative method that reveals the various events of Prophet Adam with peeling from various Qur'anic interpretations and conflict theory to express the problems faced while providing solutions for learning in a family.